An evaluation of elementary school science kits in terms of classroom environment and student attitudes - Scott, Linda F (Curtin University, 2006)
The purpose of this evaluation study was to compare students' perceptions of their science classroom environment when using science kits, textbooks or a combination of science kits, textbooks and teacher-created materials. This year-long study involved using a learning environment questionnaire, namely the My Class Inventory (MCI), interviews and observations to assess which of the three treatments leads to a more positive learning environment. Three questions investigated were whether (1) the learning environment can be reliably and validly assessed among Grade 3-5 students in Texas, (2) instruction using textbooks, science kits, or a combination of textbooks and science kits is more effective in terms of changes in student attitudes and learning environment perceptions, and (3) there are associations between student attitudes toward science classes and the classroom environment? Administrators and teachers in Texas are searching for ways to improve the scores received on standardized tests. For more than 40 years, research has shown that positive classroom environments can lead to improvement in achievement. Therefore 1 chose to investigate the above questions using a learning environments framework. This study was conducted in three urban elementary schools in North Texas. There were a total of 588 students in 28 classrooms with 16 different teachers involved in this research. The schools were similar in demographic features such as ethnicity and socioeconomic status. Analyses of data collected with the My Class Inventory (MCI) supported the instrument's factorial validity, internal consistency reliability, and ability to differentiate between the perceptions of students in different classrooms.Also, simple correlation and multiple regression analyses indicated reasonably strong and positive associations between each classroom environment scale and the students' satisfaction. The Satisfaction scale was used as an outcome variable, following the lead of Majeed, Fraser and Aldridge (2002). Results h m the MCI, interviews and observations indicated that students preferred a more positive classroom environment in terns of Cohesiveness, Competition, and Friction. Importantly, the group of students using science kits experienced greater pretest-posttest changes in satisfaction and classroom cohesiveness than did either the textbook group of the combination group. This study supports previous research that combined qualitative and quantitative methods of data collection. Qualitative methods suggested that students preferred a more hands-on presentation of science lessons rather than a textbook presentation. This was suggested in interviews with students and teachers and by observations of students in their science classes. This research evaluated three educational methods to determine which instructional method would produce a more positive learning environment and student satisfaction. These results suggest that the utilization of science kits achieves this goal as measured by student satisfaction and cohesiveness.